IMPROVISASI TORSI DAN EFISIENSI PADA REDESAIN MOTOR BRUSHLESS DC HOVERBOARD BERDAYA DASAR 350W - Adiyasa, I Wayan (Jurnal Pendidikan Vokasi Otomotif, 2023)
In the future, hoverboards are becoming a widely used means of transportation because they are compact and more practical. The hoverboard is driven by an electric motor with a fairly low power. This paper focuses on the optimization of the hoverboard BLDC motor design. The focus of the design is done by changing the stator slot depth, stator tooth width, number of strands in hand, and number of turns by keeping the fill factor below 40%. Design optimization is carried out to obtain an increase in torque performance and efficiency which has an impact on the output power of the BLDC motor and the thermal increase that occurs. The research shows torque and efficiency improvisation on the redesign of the BLDC hoverboard motor with a power of 350W. The results of the study are comparisons of torque and efficiency from comparisons of electric motor designs. The resulting temperature is analyzed to see the effect of torque, power, and efficiency.